2014
DOI: 10.1039/c4ra10784e
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in Ritter reaction

Abstract: Ritter reaction is an atom economy reaction which produces an amide through the reaction of a nitrile with an alcohol or alkene in the presence of an acid. A number of important advances have been achieved in recent years with respect to substrates, the variety of catalysts, the reaction media and the diversity of products. This paper reviews recent findings and assesses the Ritter reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 56 publications
(43 reference statements)
0
68
0
Order By: Relevance
“…These methods suffer from a few drawbacks, such as use of highly hazardous reagents, poor atom economy, forming a stoichiometric amount of byproducts and so on. To avoid these problems in amide formation, a lot of novel amide formation reactions have been explored, such as the Staudinger reaction, the Schmidt reaction, the Beckmann rearrangement, the oxidative amidation of aldehydes and alcohols, N‐ Alkylation of Amides and Ritter reaction . Among these methods, the direct transformation of nitriles to amides via Ritter reaction is a highly synthetically useful method including both available starting materials and less hazardous agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods suffer from a few drawbacks, such as use of highly hazardous reagents, poor atom economy, forming a stoichiometric amount of byproducts and so on. To avoid these problems in amide formation, a lot of novel amide formation reactions have been explored, such as the Staudinger reaction, the Schmidt reaction, the Beckmann rearrangement, the oxidative amidation of aldehydes and alcohols, N‐ Alkylation of Amides and Ritter reaction . Among these methods, the direct transformation of nitriles to amides via Ritter reaction is a highly synthetically useful method including both available starting materials and less hazardous agents.…”
Section: Introductionmentioning
confidence: 99%
“…The Ritter reaction is a simple and mild one‐pot two components strategy for amide formations involved the reaction of alcohols or suitably substituted alkenes with nitriles in the presence of a stoichiometric amount of a strong acid . The large amount of toxic and corrosive acids used in the reaction limits its application on large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the Ritter reaction of alcohols [45][46][47][48][49] and nitriles catalyzed by Brønsted acids have been reviewed; 50 and some of the results are shown in Table 4.…”
Section: Brønsted Acid-catalyzed Approachesmentioning
confidence: 99%
“…42 A general procedure allowing the conversion of tertiary alcohols with benzonitrile into tert-amides in the presence of Bi(OTf) 3 (20 mol%) as a catalyst (which was found to be the best compared with different metal triflates) in H 2 O at 100 °C for 17 h was developed by Barrett et al 115 Recent developments in Ritter reaction catalyzed by Lewis acid have been reviewed. 50 The procedure for the synthesis of amides from benzohydric alcohols and nitriles in the presence of trimesitylphosphane gold (I) complex-(Mes 3 P)AuCl with the NTf 2 -counter anion was reported by Hashmi. 116 Reactions were performed under optimized conditions (5 mol% gold (I), 5 mol% AgNTf 2 in nitrile at 75 °C) and the products were obtained in generally moderate yields.…”
mentioning
confidence: 99%
“…Oxidative CÀHa ctivation/amination reaction, [4] which takes advantage of the propensity of the benzylic CÀHb onds in H-atom abstraction( HAA), has met with some encouraging success. [7] Ritter-type reactions [8] proceed through the nitrile captureo f ac arbon cation intermediate, thusc onstituting another type of oxidative CÀHa mination strategy.F or example, Li and coworkers reporteda ni nteresting Rh-catalyzedd iamination of alkenes by acetonitrile to access imidazolines. [9] Recently,B aran et al reported ar emarkable Ritter-type intermolecular C(sp3)À Ha mination( Scheme1a).…”
mentioning
confidence: 99%